ICT in Higher Education: An Exploration of Practices in Malaysian Universities - Islam, A.Y.M. Atiquil; Mok, Magdalena Mo Ching; Gu, Xiaoqing; Spector, Jonathan; Chin, Hai Leng (Institute of Electrical and Electronics Engineers, 2019)
Information and communication technologies (ICTs) have been provided by higher education authorities to ensure that teachers use ICT to enhance their teaching, learning, and research outcomes. However, ICT has been found to be underutilized, especially by teachers. To investigate this issue, the technology adoption and gratification (TAG) model was validated and used to examine Malaysian university teachers' adoption and gratification of ICT for teaching and research purposes and then used to investigate the moderating effect of universities in different regions. The 397 teachers from the west and east Malaysian universities were surveyed using a stratified random sampling technique. The research data were analyzed using the three-stage structural equation modeling. There were focused use factors: 1) academic purpose; 2) research purpose; and 3) teaching purpose. The TAG model was useful in explaining differences in ICT uses. West Malaysian teachers' perceived usefulness and ease of use mediated the relationships between computer self-efficacy, gratification, and intention to use ICT, respectively. However, for east Malaysian teachers, only perceived ease of use did not mediate the relationship between computer self-efficacy and gratification. Finally, west and east Malaysian teachers' intentions to use ICT mediated the relationships between actual use, perceived usefulness, and ease of use. This paper confirms the utility of the TAG model for comparing teachers' adoption and gratification of ICT. In addition, this paper provides a basis for the targeted professional development of teachers in the east and west Malaysian universities which were selected based on the known differences. © 2019 IEEE.